Cosmological Inflation and the delta N formalism - Fransson, Emil (My University, 2011)
In this thesis we perform a study of cosmological inflation in the delta-N-formalism. Inflation is a period of time when the physical distances in the universe grew immensely. Most theories of inflation use one or more scalar fields to drive inflation. Through Fluctuations in these fields one can get theoretical predictions of the anisotropies in the Cosmic Microwave Background radiation by using the so called delta-N-formalism.
Keywords: Grundläggande vetenskaper; Kosmologi; Basic Sciences; Cosmology